A randomized, double-blind, placebo-controlled pilot study to evaluate the efficacy and tolerability of a novel oral bioadhesive formulation for the treatment of nonerosive reflux disease-related symptoms. Issue 2 (February 2021) - Ribaldone, Davide Giuseppe; Rajesh, Pendlimari; Chandradhara, Divya; Astegiano, Marco; Pellicano, Rinaldo
Abstract : Objective: The use of antisecretory drugs can provide symptomatic relief in 70–80% of patients suffering from gastro-oesophageal reflux disease (GORD), although this benefit is reduced by 20–30% in the case of nonerosive reflux disease (NERD). The current study evaluates the efficacy and safety of a patented oral formulation (liquid sachets containing hyaluronic acid, a mixture of amino acids including proline, hydroxyl-proline and glutamine, and rice extract dispersed in a bioadhesive polymer matrix) for relieving the symptoms of NERD. Methods: A single-centre, randomized, double-blind, parallel group, placebo-controlled clinical study was performed. Patients who experienced at least three episodes of moderate-severity heartburn during the 7-day run-in period were included and treated with three liquid sachets per day for 14 days. The primary objective was to evaluate the proportion of patients with at least a three-point reduction in the total symptom score (TSS). Results: Overall, 20 patients were randomized to receive the investigational product and 20 to receive the placebo. At the end of treatment, a three-point reduction in the TSS was achieved by 95% of patients treated with the investigational product and by 20% of patients treated with placebo ( P < 0.0001). No adverse events were reported. Conclusion: The investigational product showed a statistically significant superiority to the placebo in relieving common symptoms in patients with NERD. Future studies will be aimed at clarifying the hypothesis that this symptomatic benefit is related to the strengthening of the oesophageal barrier against the damage induced by gastric contents.